Photos in Transmotion: Images of Survivance in Ledfeather - Turner, Alison (Transmotion, 2023)
Stephen Graham Jones’ Ledfeather (2008), a semi-epistolary, semi-historical novel, poses questions about how historical knowledge is made and what to do with it. While scholars have studied the novel’s postmodern attributes as methods for subversive critiques of historiography in indigenous colonial contexts, as of yet no study prioritizes the novel’s use of photographs toward these aims. After situating the novel’s engagement with photographs into histories of photography and indigenous colonization, I examine the rhetorical role of these photos in the complex Ledfeather narrative. Guided by Gerald Vizenor’s framing of “the indian [as] poselocked in portraiture” (Fugitive Poses 146), I argue that the photos enact Vizenor’s sense of transmotion, or “the tease of creation in pictures, memories, and stories” (Fugitive Poses 173). I end by considering the rhetorical relationships between images and words both in archival collections that are specific to these histories and in Ledfeather as postmodern historical fiction.